Teoria i praktyka celebrytyzacji politycznej. Celebryci polityczni w internetowych serwisach plotkarskich - Olczyk, Tomasz (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2013)
Celebrities are becoming a subject of growing interest for researchers and journalists. Studies on fame and popularity have become a separate research field with its own academic periodical. There are emerging books devoted solely to celebrities in the world of politics discussing the phenomenon of the increasing role of fame in modern politics, given the context of tabloidization, post-politics or the ‘entertainization’ of politics. Although the corpus of literature dealing with studies on political celebrities is increasing, this field continues to struggle with at least two fundamental issues. The first difficulty concerns the operational application of the concept of celebrity to describe the realm of politics. The second one concerns the limited number of empirical analyses of the phenomenon of political celebritization. The aim of this paper is to begin to fill this gap. The first part analyzes terminological difficulties concerning the concept of political celebrity. Next, the author suggests a new approach to this concept.